2014
DOI: 10.1016/j.jvs.2014.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes reported by the Vascular Quality Initiative and the National Surgical Quality Improvement Program are not comparable

Abstract: VQI and NSQIP demonstrate substantial concordance for most preoperative variables and poor concordance for most postoperative variables, even at identical collection periods. This discordance is a result of differences in data collection methods and variable definitions. On the basis of these findings, VQI and NSQIP data sets cannot be used to directly compare risk-adjusted patient outcomes between institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
2
17
0
3
Order By: Relevance
“…11 When this factor is eliminated by using identical collection periods, differences in variable definition and variable collection result in discordance in postoperative variables and outcomes. 12 The unique continuous data-collection method employed by the VQI and the 1-year follow-up data allow for a more complete review of procedural and long-term−outcome activity at each institution.…”
Section: Discussionmentioning
confidence: 99%
“…11 When this factor is eliminated by using identical collection periods, differences in variable definition and variable collection result in discordance in postoperative variables and outcomes. 12 The unique continuous data-collection method employed by the VQI and the 1-year follow-up data allow for a more complete review of procedural and long-term−outcome activity at each institution.…”
Section: Discussionmentioning
confidence: 99%
“…16 As expected, in our study, the main risk factor for periprocedural MI was a history of coronary artery disease. The risk of periprocedural MI has never been compared in lower extremity artery between surgery and angioplasty/stenting; only few studies [30][31][32] reported this risk after surgery and only 1 33 after angioplasty/stenting. Thus, uncertainty remains on whether our results are specific or not of the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…Так, по данным одного из метаанализов, частота развития неблагоприятных коронарных событий была значи-тельно выше после проведения КЭЭ, по сравнению с каротидной ангиопластикой со стентированием, что связывалось с назначением двойной антитром-боцитарной терапии после стентирования, а также активацией провоспалительных цитокинов и про-тромботического состояния в результате открытого хирургического вмешательства -каротидной эндар-терэктомии [10,11]. По данным ряда зарубежных ав-торов, важнейшим предиктором развития инфаркта миокарда (ИМ) является наличие реваскуляризации одного из сосудистых бассейнов ранее, что подчер-кивает значимость мультифокального атеросклероза (МФА) как системного заболевания [12,13]. В ряде исследований было также отмечено, что факторами риска развития неблагоприятных событий и леталь-ного исхода после КЭЭ и каротидной ангиопластики со стентированием являются контралатеральная ок-клюзия внутренней сонной артерии (ВСА) и пожилой возраст [10].…”
unclassified